Mucormycosis in children with hematological and oncological diseases in saint-petersburg - N. N. Klimko; S. N. Khostelidi; E. G. Boychenko; A. S. Kolbin; A. G. Volkova; M. O. Popova; T. S. Bogomolova; L. S. Zuborovskaya; M. B. Belogurova; N. V. Medvedeva; B. V. Afanasyev (Журнал инфектологии, 2016)
In prospective multicenter study were included 20 pediatriconcohematologic patients with mucormycosis. Age: 3 – 17 yy (median – 11), females – 60%. The diagnosiswas made according to EORTC/MSG 2008 criteria (post mortem – 25%). The main underlying disease was acutel eukemia (70%), risk factors – prolong severe neutropenia (median – 31 d) and lymphocytopenia (median – 33 d) after cytostatic chemotherapy or hematopoietic stem cells transplantation. Etiology agents were Lichtheimia corуmbifera, Rhizopus spp. and Rhizomucor spp. Main sites of infection were lungs (65%) and paranasal synuses (30%), dissemination – 45%. Antifungal therapy (amphotericin B lipid coplex, posaconazole, caspofungin, amphotericin B) was used in 75% patients, surgery – 30%. Overall mortality in 12 weeks was 70%.